The Impact of External Capital on the Performance of Agricultural Cooperatives in Indonesia - Sunarwibowo, Rizki Pratomo; Mohamad Ikhsan; Benedictus Raksaka Mahi; I Dewa Gede Karma Wisana (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: Sufficient capital remains a notable challenge across various business models. This study investigates the influence of capital, mainly external capital, on cooperative productivity. Background Problems: Cooperatives are viewed as a potential avenue for supporting the public economy and establishing a fundamental pillar within a robust economic structure. However, in Indonesia, cooperatives have not fully realized these envisioned prospects. The issue of access to capital is believed to have an impact on the productivity of cooperatives. Novelty: Limited research has delved into the impact of capital on cooperative productivity. Our study utilized cooperative firm-level data, while the majority of prior studies have relied on less-detailed aggregate data. Research Methods: We employed recent data on agricultural cooperatives in Indonesia, covering 3,315 units. The endogenous switching regression method was applied to estimate the impact of external capital on cooperative productivity and draw comparisons between cooperatives that embraced external capital and those that did not. Finding/Results: The results indicated that cooperatives utilizing external capital exhibited a 2.8% higher level of productivity than those that did not. Additionally, we explored the impact of external capital based on cooperative size. The results revealed that large-category cooperatives experienced a 10% increase in productivity, medium-category cooperatives a 5.6% increase, small-category cooperatives a 0.8% increase, and micro-category cooperatives a 0.1% increase. Conclusion: These findings underscore the substantial influence of capital factors, mainly external capital, on cooperative productivity. The government needs to enact legislation to better regulate and support access to capital.